PENGARUH THE HIJAU DAN THE HITAM DALAM MINUMAN THE KEJU TERHADAP BOBOT BADAN DAN RISIKO DIABETES MELITUS PADA MENCIT SWISS WEBSTER JANTAN - Neng Fisheri Kurniati; Rosyadi Amelia Try Yuliani (Acta Pharmaceutica Indonesia, 2022)
Cheese tea contains two main ingredients, tea, and dairy products. Green tea, black tea, and dairy products in the cheese tea have been shown to have beneficial effects on both body weight and blood glucose. However, there is no evidence that this benefit also applies to cheese tea. Moreover, cheese tea drinks which are sold in the market may be added with sugar to enhance flavor. This study aims to identify the effect of green tea and black tea in cheese tea on body weight and the risk of diabetes mellitus. The research was conducted with experiments on 32 male Swiss Webster mice which were divided into eight groups, namely the negative control (water), positive control (dextrose), and treatment group consisting of cheese green tea or cheese black tea groups with different compositions of sugar. The test drinks were administered once a day orally for 21 days. The results of this study showed that cheese green tea or cheese black tea affected blood glucose, but not body weight. Consumption of normal sugar cheese black tea and half sugar cheese black tea showed a significant increase in blood glucose compared to negative control, so there is a risk of developing diabetes mellitus. Meanwhile, consumption of unsweetened cheese tea and half-sugar cheese green tea did not increase blood glucose levels significantly compared to negative control. In conclusion,  consumption of cheese tea with green tea shows a better effect on blood glucose.